Impact of smart healthcare on the physical and mental health of older adults Chinese patients with chronic diseases under the background of “Internet Plus”: analysis of data from the China family panel studies - Xie, Fanbao; Liang, Xinyi; Guan, Xin; Ji, Peng; Cao, Xiaojing; Liao, Jiarong (Frontiers in Public Health, 2025)
ObjectiveThis study was to investigate the impact of smart healthcare on the physical and mental health of older adults chronic disease patients in China.MethodsData from 6,092 chronic disease patients were collected from the 2022 China family panel studies (CFPS). Participants were rolled into two groups based on whether they utilized Internet Plus-based smart healthcare technology for chronic disease management: the usage group (n = 2093) and the non-usage group (n = 3,999). A comparison was conducted between the two groups in terms of activities of daily living (ADL) scores, self-rated health (SRH), and the center for epidemiologic studies depression scale (CES-D). Furthermore, a multivariate logistic regression analysis was employed to identify the risk factors influencing the physical and mental health of patients in the usage group.ResultsPost-intervention, the SRH and ADL scores of the usage group were greatly superior to those of the non-usage group, while the CES-D scores were greatly lower (p < 0.05). Samples with chronic disease duration exceeding 10 years demonstrated the lowest SRH and ADL scores and the highest CES-D scores (p < 0.05). Similarly, samples experiencing chronic pain exhibited the lowest SRH and ADL scores and the highest CES-D scores (p < 0.05). Samples with an income level below 10,000 yuan per annum demonstrated the lowest SRH and ADL scores and the highest CES-D scores (p < 0.05). Additionally, individuals with an educational attainment of primary school or below exhibited the lowest SRH and ADL scores and the highest CES-D scores (p < 0.05). Chronic disease duration exceeding 10 years and chronic pain were identified as significant risk factors affecting ADL and CES-D scores. Chronic disease duration exceeding 10 years, chronic pain, an income level below 10,000 yuan per annum, and an educational attainment of primary school or below were identified as risk factors for SRH scores (p < 0.05).ConclusionWith the assistance of Internet Plus-based smart healthcare, the physical and mental health of older adults chronic disease patients in China can be effectively improved. However, the influence of longer chronic disease duration, chronic pain, low income, and low educational attainment on the effectiveness of smart healthcare assistance should be considered.